(untitled) (Applied Biological Research, 2020)
Several models of rice transplanters are available in the market to ease the transplanting work. However, the safety and efficiency aspects of these transplanters with respect to women workers has not been studied. Therefore, the present study was aimed to ergonomically evaluate the commercially available three models of rice transplanters viz., Redlands 8 row riding type transplanter, Mahindra 4 row walking type transplanter and Manual 2 row transplanter. A significant variation in heart rate and energy expenditure in the operation of different models of transplanters was observed. Heart rate was lowest in Redlands 8 row riding type transplanter (110.5 beats min-1) and maximum in traditional method of transplanting (148.5 beats min-1). The average heart rate before 9 am was 119.9 beats min-1 whereas after 11 am it increased to 142.8 beats min-1. Overall discomfort score varied from 3.0 to 8.4 and were scaled as " light discomfort" to "more than moderate discomfort" for selected operations. The body part discomfort score was maximum (46.8) in transplanting manually and minimum in transplanting with Redlands 8 row riding type transplanter (20.15). The work rest cycle was 30 min work followed by 2 min rest for Redlands 8 row riding type rice transplanter, 9 min rest for Mahindra walking type, 12 min rest for manual transplanter and 14 min rest for traditional method. Based on these results it was found that 8 row riding type transplanter was more suitable and ergonomically comfortable for the women operators.